DSTATCOM Control Algorithms: A Review - Ambarnath Banerji; Sujit K. Biswas; Bhim Singh (Institute of Advanced Engineering and Science, 2012)
The concept that an inverter can be used as a generalized impedance converter to realize either inductive or capacitive reactance has been widely used to mitigate power quality issues of distribution networks. One such device is the DSTATCOM which is connected in shunt at the load end. The heart of the DSTATCOM is a converter. The control algorithm of the converter is very important. It causes the converter to address the power quality problems in efficient manner. This paper discusses the various control algorithms of the converter. The manners in which the power quality issues are mitigated by the converter are also explored. Simulations of the control algorithms are made on MATLAB platform to ascertain the effectiveness of each control method for power quality mitigation.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.515